2022
DOI: 10.3389/fonc.2022.916375
|View full text |Cite
|
Sign up to set email alerts
|

Complex metabolic interactions between ovary, plasma, urine, and hair in ovarian cancer

Abstract: Ovarian cancer (OC) is the third most common malignant tumor of women accompanied by alteration of systemic metabolism, yet the underlying interactions between the local OC tissue and other system biofluids remain unclear. In this study, we recruited 17 OC patients, 16 benign ovarian tumor (BOT) patients, and 14 control patients to collect biological samples including ovary plasma, urine, and hair from the same patient. The metabolic features of samples were characterized using a global and targeted metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…In a prospective nested case-control study, Wang S conducted an untargeted metabolomics study in subjects with incident pancreatic cancer (n = 68) and matched controls (n = 136) and the results showed that alanine was signi cantly associated with an increased risk of pancreatic cancer (Wang 2022). Moreover, in another study, the concentration of alanine in plasma and urine of the control group was lower than that of ovarian cancer (Zhong 2022). In a case-control study, statistically signi cant differences in serum alanine levels were found in patients with prostate cancer compared to the control group (Dereziński 2017).…”
Section: Discussionmentioning
confidence: 88%
“…In a prospective nested case-control study, Wang S conducted an untargeted metabolomics study in subjects with incident pancreatic cancer (n = 68) and matched controls (n = 136) and the results showed that alanine was signi cantly associated with an increased risk of pancreatic cancer (Wang 2022). Moreover, in another study, the concentration of alanine in plasma and urine of the control group was lower than that of ovarian cancer (Zhong 2022). In a case-control study, statistically signi cant differences in serum alanine levels were found in patients with prostate cancer compared to the control group (Dereziński 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Alterations in cellular metabolism have been reported in numerous human cancers and are thought to re ect the metabolic demands related to cancer development (Zhong et al, 2022). In this study we performed comprehensive metabolic pro ling of plasma exosome samples collected from 105 women diagnosed either with OC, BE, or controls (CON).…”
Section: Overall Changes In Metabolite Pro Lesmentioning
confidence: 99%
“…Other studies have found similar metabolic alterations in OC. Speci cally, Zhong et al observed an upregulation of glutathione metabolism in women diagnosed with this malignancy (Zhong et al, 2022). Elevated glutathione metabolism has been shown to accompany tumor growth, presumably to counteract the increased oxidative stress arising from accelerated metabolic rates(Huang et al; Gamcsik et al, 2012;Zhong et al, 2022).…”
Section: Metabolic Pathway Enrichment Analysismentioning
confidence: 99%
“…The noninvasive nature of hair sample collection reduces patient discomfort and allows for easier and more frequent sampling. Indeed, hair has been recently applied in discovering disease biomarkers in clinical research. , Additionally, the distribution of chemical compound concentrations along the hair shaft reflects changes in the corresponding composition during the measurement period. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, hair has been recently applied in discovering disease biomarkers in clinical research. 9,18 Additionally, the distribution of chemical compound concentrations along the hair shaft reflects changes in the corresponding composition during the measurement period. 10,19,20 In this study, we aimed to perform a high-resolution mass spectrometry (HRMS)-based untargeted and targeted metabolomic approach on hair samples from 6-month-old 5xFAD mice, characterized by accumulation of amyloid plaques in the brain.…”
Section: ■ Introductionmentioning
confidence: 99%